Nomenclature of the triphylite group of minerals - L. M. Lyalina; E. A. Selivanova; F. Hatert (European Journal of Mineralogy, 2023)
In this paper we present a Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (IMA-CNMNC)-accepted scheme for the classification and nomenclature of the triphylite group of minerals. The general formula of those minerals is M1M2TO4, where M1 and M2 refer to cations in an octahedral coordination: M1 = □, Na, Li; M2 = Mn2+, Fe2+, Mg, Fe3+, Mn3+, and T to tetrahedrally coordinated P5+ cations. The group contains the Li-bearing phosphates triphylite [LiFe2+(PO4)] and lithiophilite [LiMn2+(PO4)] and their oxidation products heterosite [Fe3+(PO4)] and purpurite [Mn3+(PO4)], as well as the Na-bearing phosphates natrophilite [NaMn2+(PO4)] and karenwebberite [NaFe2+(PO4)]. The Li–Mg-bearing phosphate simferite has been redefined as LiMg(PO4). Ferrisicklerite and sicklerite correspond to intermediate phases in the triphylite–heterosite and lithiophilite–purpurite solid solutions; consequently, according to the CNMNC dominant-constituent rule, they are discredited. A new mineral oxidation sequence is defined, which considers the different oxidation capacity of iron and manganese, and therefore replaces the traditional Quensel–Mason sequence. The formula calculation procedure for Li-bearing species, based on electron microprobe analyses and single-crystal X-ray diffraction data, is also described.